Heterobilayers of 2D materials as a platform for excitonic superfluidity - Sunny Gupta (Nature Portfolio, 2020)
Here, the authors screen hundreds of 2D materials and identify the candidates where spontaneous excitonic condensation mediated by purely electronic interaction should occur in true equilibrium. Hetero-pairs Sb2Te2Se/BiTeCl, Hf2N2I2/Zr2N2Cl2, and LiAlTe2/BiTeI emerge as promising.